2021
DOI: 10.1099/acmi.0.000173
|View full text |Cite
|
Sign up to set email alerts
|

A case report: insights into reducing plastic waste in a microbiology laboratory

Abstract: Single-use plastics have often replaced more sustainable materials in microbiology laboratories. Keeping in mind that one of the objectives of the United Nations Sustainable Development Goals is responsible consumption and production, we wanted to document how many single-use plastic items could be saved by taking reduction and reuse approaches in a microbiology laboratory. After taking 4 weeks to document the baseline levels of single-use plastic waste being generated in our laboratory and identifying ways to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 11 publications
(13 reference statements)
0
43
0
1
Order By: Relevance
“…The generation of plastics waste by water quality testing conducted to monitor progress toward SDG 6.1 is somewhat at odds with SDG goal 12.6, established to “substantially reduce waste generation through prevention, reduction, recycling, and reuse.” 29 Plastics waste generated by scientific research is non-negligible; the University of Exeter bioscience department estimated their plastic waste consumption to be approximately 247 tonnes in 2014 30 —generated in 1 year by 1 department laboratory in 1 university. There have been calls to reduce consumption of single-use plastic items in laboratory work, 30 for example by re-using items such as pipettes 5 or recycling nitrile gloves 6 if possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of plastics waste by water quality testing conducted to monitor progress toward SDG 6.1 is somewhat at odds with SDG goal 12.6, established to “substantially reduce waste generation through prevention, reduction, recycling, and reuse.” 29 Plastics waste generated by scientific research is non-negligible; the University of Exeter bioscience department estimated their plastic waste consumption to be approximately 247 tonnes in 2014 30 —generated in 1 year by 1 department laboratory in 1 university. There have been calls to reduce consumption of single-use plastic items in laboratory work, 30 for example by re-using items such as pipettes 5 or recycling nitrile gloves 6 if possible.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidance on reducing laboratory plastic waste generally assumes access to a centralized laboratory, recycling program infrastructure, and/or high-cost items such as an autoclave, 5 , 6 thus reducing the potential for plastic waste reduction to be realized in low-resource and portable applications such as the MICS water quality tests. Therefore, the objective of this study was to evaluate different re-use protocols for disposable filter funnels used by the MICS water quality test.…”
Section: Introductionmentioning
confidence: 99%
“…One way of achieving this is through green certification e.g., via My Green Lab or ISO 14001. Many laboratories are recognising the need to operate in more sustainable ways and have implemented changes to working practices to reduce their waste and energy consumption [23][24][25]. Successful transitioning to such work practices is achieved through staff engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the ease and accessibility to single-use plastics has grown dramatically over the past decades, to the point of reliance 14 . Several studies from clinical environments have shown that reusable materials typically result in lower carbon footprints, and reduce financial costs 12,15 .…”
Section: Introductionmentioning
confidence: 99%
“…While incineration, in most cases, recovers part of the calorific value of single use equipment, it remains a carbon intensive and unsustainable process 11 . To mitigate these impacts, many labs have initiated efforts to improve the recycling of laboratory plastics 12 . Beyond recycling, some laboratories have introduced techniques to reduce the impact of single-use plastic consumption, including reduction and re-use of materials 13 .…”
Section: Introductionmentioning
confidence: 99%